Biopsychosocial Determinants of Visual Inspection Acetic-Acid Test Uptake in Sragen, Central Java - Saptowati, Dewi; Mudigdo, Ambar; Murti, Bhisma (Journal of Maternal and Child Health, 2018)
Background: Cervical cancer ranks second among the top ten leading causes of death in women in the world, especially in developing countries. Cervical cancer can be cured if detected early. A simple and common method in early detection of cervical cancer is a visual inspection acetatic-acid (VIA) test. This study aimed to analyze the biopsychosocial factors associated with use of VIA test, using health belief model and a path analysis model. Subjects and Method: This was an analytic observational study with a cross-sectional design. The study was carried out in Sragen, Central Java, from October 2017 to May 2018. A sample of 200 women was selected by fixed disease sampling. The dependent variable was utilization of VIA test. The dependent variables were intention, self-efficacy, perceived benefit, perceived barrier, attitude, subjective norm, knowledge, education, perceived susceptibility, perceived seriousness, and number of children. Data on VIA test were obtained from medical record. The other variables were measured by questionnaire and analyzed by path analysis. Results: Use of VIA test was directly and positively affected by intention (b= 3.50; 95% CI= 1.20 to 5.79; p=0.003), perceived benefit (b= 5.21; 95% CI= 1.98 to 8.44; p= 0.002), and number of children (b= 4.23; 95% CI= 1.61 to 6.86; p<0.001). Use of VIA test was directly and negatively affected by perceived barrier (b=-5.98; 95% CI= -8.83 to -3.13; p<0.001). Use of VIA test was indirectly affected by attitude, subjective norm, self-efficacy, knowledge, education, perceived susceptibility, and perceived seriousness. Conclusion: Use of VIA test is directly and positively affected by intention, perceived benefit, and number of children, but negatively affected by perceived barrier. Keywords: visual inspection acetic-acid test, determinants, biopsychosocial, health belief model Correspondence: